Odontogenic abscess with severe and fast evolution in a young and healthy patient - Bruna da Fonseca Wastner; Salmo Cortiglio; Joana Letícia Vendruscolo; José Luis Dissenha (Universidade Estadual de Campinas, 2018)
Deep cervical abscesses are infections of the different spaces on the the neck that may have a mild or severe outcome and requires fast and assertive approach. The most usual cases of severe infections are associates with comorbidities and older patients, but sometimes, in rare cases, it may affect the younger and healthier. Aim: The purpose of this is to communicate shortly a case of a severe cervical abscess with fast evolution in a 28 years old patient, to highlight the possibility of this outcome even in unexpected cases.